THE INFLUENCE OF DIGITAL MARKETING AND INTELLECTUAL CAPITAL ON ORGANIZATIONAL PEFORMANCE WITH CONSUMER SATISFICATION AS A MODERATING VARIABLE - Sudirjo, Frans; Kalalo, Rieneke Ryke; Utami, Eva Yuniarti; Sulastri, Tuti; Putra, Wira Pramana (JURNAL ILMIAH EDUNOMIKA, 2024)
Organizational performance is the thing that companies pay the most attention to and is the most important goal compared to other goals that must be well maintained and achieved by an organization/company. There are a number of factors that can influence organizational performance, including digital marketing and intellectual capital. In contrast to a number of previous studies, this research adds the Consumer Satisfaction variable which the researchers believe can strengthen the influence of the independent variable on the dependent variable used in this research. This research is quantitative research with an explantory approach. In this research, primary data was distributed to 250 employees of PT. Indofood with employee criteria in the fields of HRD, Human Resources and Finance spread throughout Indonesia. The data used was analyzed with smart PLS 3.0 software. The results of this research show that the Digital Marketing and Intellectual Capital variables have a positive relationship and have a significant influence on the Organizational Performance variable because the p-values are below the significance level and point in a positive direction. Apart from that, the Consumer Satisfaction variable can moderate the relationship between the Digital Marketing variable and the Organizational Performance variable and the Intellectual Capital variable with the Organizational Performance variable Keywords: Digital Marketing, Intellectual Capital, Organizational Peformance, Consumer Satisfication